Graphics in Physics Research Articles - Keng-Soon Soo (Journal of Modern Languages)
This study investigates the use of one component of scientific writing, that is, graphics, such as figures, tables, diagrams, graphs und pictures in one type of scientific texts - Physics research articles. It also attempts to find out how these graphics are linked to the texts themselves. The paper shows that graphics are a significant part of Physics research articles, which tends to occur in the results and method sections of these articles. In addition, graphics are integrated and linked to these research articles with very rigid structures. Thus, it is possible to teach writing of graphics, at least in a fairly formulaic way.